SAT0216 PATIENT PERCEPTIONS OF PHYSICAL ACTIVITY AFTER A DIAGNOSIS OF GIANT CELL ARTERITIS: A SECONDARY ANALYSIS OF MULTINATIONAL QUALITATIVE DATA. (June 2019) - Austin, Keziah; Dures, Emma; Almeida, Celia; Cramp, Fiona; Gilbert, Kate; Guly, Catherine; Hill, Catherine; Mackie, Sarah; O'brien, Anne; Watts, Richard; Robson, Joanna
Abstract : Background: Giant cell arteritis (GCA) is the most common vasculitis in the UK, with an incidence of 220 cases/million in adults over 50 years of age. The physical symptoms as well as the side effects of glucocorticoids may impact patients' ability to exercise. Maintaining physical activity (PA) has been shown to be beneficial to disease activity in other inflammatory conditions, and is also a specific priority for GCA patients. Objectives: To explore patient perceptions of physical activity in GCA. Methods: Multinational qualitative study, using interviews with 36 patients from the UK (25) and Australia (11), all of whom had a definitive diagnosis from imaging or biopsy. Interviews were recorded, transcribed, and analysed using inductive thematic analysis. This is secondary analysis of data collected to explore health-related quality of life in people with GCA. Results: 84 individual themes were reported by patients, each of which fell broadly into two overarching themes: barriers to and facilitators of physical activity. Within each theme, four subthemes were identified. In terms of barriers, these were: negative physical symptoms (including visual loss, fatigue, weakness, pain and stiffness), lack of physical capability (including poor stamina, confidence and mobility), negative perceptions around PA, and negative reinforcement (i.e. new physical symptoms following PA). Facilitators of physical activity were also grouped into four subthemes: external facilitators (including motivation from healthcare professionals and support groups), access to appropriate facilities, personal strategies (including pacing and goal-setting) and personal facilitators (including internal motivation to improve symptoms, and positive reinforcement from PA). Conclusion: There are a variety of barriers to physical activity in GCA patients, including patients being fearful of exercise. In other inflammatory conditions, patients report improved symptoms following physical activity as well as wider benefits to general wellbeing and cardiovascular health. Education, motivational interviewing, and personalised strategies may be beneficial components of an intervention to support physical activity in patients with GCA. References: [1] Hellmann DB, Uhlfelder ML, Stone JH, Jenckes MC, Cid MC, Guillevin L, et al. Domains of health-related quality of life important to patients with giant cell arteritis. Arthritis Care Res 2003;49(6):819-25 [2] Perandini LA, de Sa-Pinto AL, Roschel H, Benatti FB, Lima FR. Bonfa E & Gualano B. Exercise as a therapeutic tool to counteract inflammation and clinical symptoms in autoimmune rheumatic diseases. Autoimmun Rev 2012;12(2)218-24 [3] Smeeth L, Cook C & Hall AJ. Incidence of diagnosed polymyalgia rheumatic and temporal arteritis in the United Kingdom, 1990-2001. Ann Rheum Dis 2006;65(8):1093-98 Disclosure of Interests: Keziah Austin: None declared, Emma Dures Grant/research support from: Has previously received an independent learning grant from Pfizer, however the work has been completed and the grant has been closed., Celia Almeida: None declared, Fiona Cramp: None declared, Kate Gilbert: None declared, Catherine Guly: None declared, Catherine Hill: None declared, Sarah Mackie: None declared, Anne O'Brien: None declared, Richard Watts: None declared, Joanna Robson: None declared